Inorganic Waste Reduction Planning with The Implementation of Dipo Waste Bank (DWB) and Reverse Vending Machine (RVM) at Diponegoro University - Sri Sumiyati; Mochamad Arief Budihardjo; Bimastyaji Surya Ramadhan; Budi Warsito; Hanif Kusumasasmita; Ghifar Rahman; Hizkia Christian Putra Setiadi (Universitas Diponegoro, 2023)
Plastic waste is a global environmental problem that has existed for a long time and has not been resolved. On a worldwide scale, solid waste increased to 9.1 billion tons, of which 6.9 billion tons was plastic waste. Undip is one of the largest public universities. As one of the universities that supports the achievement of SDGs Number 12 concerning waste management, Diponegoro University has a Waste Bank, namely the Dipo Waste Bank (DWB). The method used in this study is mass balance. Based on the projected waste generation from 2021-2030, the era of inorganic waste in the composition of plastic bottles at Undip is 42,577 kg/day. DWB is expected to realize independent and sustainable waste management within Diponegoro University (UNDIP). In its course, waste management efforts are felt to be lacking due to several obstacles and participation that are not optimal. There are three scenarios of reducing inorganic waste of plastic bottles in the study, namely the baseline scenario, the Dipo Waste Bank (DWB) scenario can achieve the target of 20% of waste that can be recovered by DWB and Reverse Vending Machine (RVM).